Uric Acid Level Examination in the Elderly Using the POCT Method to Analyze Factors Associated with Hyperuricemia - Erdanela Setiawati (Postgraduate, University of Mataram, 2025)
The importance of uric acid level testing in the elderly lies in prevention and early management efforts. Point-of-Care Testing (POCT) allows for rapid and easy screening in the community. Although the pathophysiology of hyperuricemia involves decreased renal excretion of uric acid due to aging, this condition is also strongly influenced by various external and internal risk factors. Risk factors commonly associated with hyperuricemia include demographics (age, gender), lifestyle (high-purine diet, physical activity), genetic factors (family history), and the presence of comorbidities. This observational-analytical study with a cross-sectional design aimed to examine uric acid levels and identify seven risk factors and pain symptoms in elderly people (≥ 60 years) in Nagari Pakan Rabaa Timur, South Solok, West Sumatra. The examination was conducted using the POCT (GCU-meter) method on a sample of 87 elderly people taken by purposive sampling. The results showed that the majority of elderly people (58.60%) experienced hyperuricemia (high uric acid levels), which confirms the elderly's vulnerability to this condition due to degenerative processes. Demographically, the sample was dominated by the Young Elderly group (60-69 years, 56.30%), women (66.70%), and had a low level of education (95.40%). Other common risk factors were a high-purine diet (57.50%) and a history of hypertension (40.20%). The majority of elderly people also reported pain symptoms (81.60%), with the level of pain felt mostly being severe (34.5%).